Culicidae and Ceratopogonidae (Diptera: Nematocera) inhabiting phytotelmata in Iguazú National Park, Misiones Province, subtropical Argentina - Campos, Raul Ernesto (2011)
A list of the most common phytotelmata and their Culicidae and Ceratopogonidae inhabitants from Iguazú National Park, Misiones Province, Argentina, is presented, and biological and behavioral observations are also included. Species of Poaceae, Bromeliaceae, Apiaceae, Araceae, Urticaceae, Marantaceae, and Arecaceae, were identified as phytotelmata. Twenty six species of Culicidae and nine of Ceratopogonidae were identified. The highest species richness of culicids and ceratopogonids was recorded from the bamboo Guadua chacoensis (Poaceae) and treeholes, respectively. Fourteen species of Culicidae and three of Ceratopogonidae inhabit bamboo, two and five treeholes, seven and three bromeliads, and nine and one, other less known phytotelmata, respectively.